Macroeconomic disasters and consumption smoothing: International evidence from historical data - Lorenzo Pozzi; Barbara Sadaba (Bank of Canada, 2023)
This paper uses a large historical dataset (1870-2016) for 16 industrial economies to show that during macroeconomic disasters (e.g., wars, pandemics, depressions) aggregate consumption and income are significantly less decoupled than during normal times. That is, during these times of turmoil, the consumer intertemporal budget constraint holds more strictly, implying a structural reduction in consumption smoothing. While we also observe this for the ongoing COVID-19 pandemic, this is not the case for more conventional post-war recessions. Our results are obtained using a predictive regression approach that follows directly from the forward-looking nature of consumption theory. Using a savers-spenders type of model, we show that our findings can be interpreted as stemming from an increase in rule-of-thumb consumer behavior during disasters as well as from a stronger precautionary savings motive of optimizing consumers.
Keywords: E21; C23; 330; Business fluctuations and cycles; Coronavirus disease (COVID-19); Econometric andstatistical methods